Hadhrami ‘ulama’ within the Malay-johor activism: the role of Sayyid ‘Alwi Bin Tahir Al-haddad (1934-1961) - Fauzi, N. (IDOSI Publications, 2013)
Sayyid ‘Alw Bin Tahir al-Haddad was one of the most prominent overseas Hadhrami in the late nineteenth century. He became the leading ‘ulama’ among the Hadhrami in that era due to his renowned intellectuality in many places in the Islamic world such as South Africa, Singapore, Indonesia and in Malaya.According to R.B Serjeant, Sayyid ‘Alw was remarkable in terms of his achievements and prominence, as well as being well-versed in the Islamic jurisprudence and Islamic education. He also played crucial roles in the study of Islamic literacy, politics and history, which were the determining elements in championing the Malay supremacy in Johor from 1964-1961. Viewing Sayyid ‘Alw ’s remarkable achievements, his contribution in various fields were clearly significant, particularly so when it comes to transforming perspectives either in Islamic administrations or in educations among the Malay-Johor people. This paper will consider the life of a Hadhrami ‘ulama’; Sayyid ‘Alw ’s life, career and contributions towards the Malay-Johor activism in the late nineteenth century, in the wake of Islam. Along the way, this essay will briefly explore the many points he had expressed, especially Islamic reformist ideas through various media such as religious works, educations and journalistic writings.